2017
DOI: 10.1111/bph.13928
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of JNK signalling mediates PPARα‐dependent protection against intrahepatic cholestasis by fenofibrate

Abstract: These data suggest that the protective effects of fenofibrate against cholestasis-induced hepatic injury are dependent on PPARα and fenofibrate dose, and are mediated through inhibition of JNK signalling. This mechanism of fenofibrate protection against intrahepatic cholestasis may offer additional therapeutic opportunities for cholestatic liver diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 72 publications
3
37
0
Order By: Relevance
“…Some pilot studies demonstrated the efficacy of fenofibrate and ursodeoxycholic acid combination in patients with primary biliary cirrhosis (Ghonem & Boyer, ; Zhang et al, ). Furthermore, fenofibrate could protect ethinylestradiol and chlorpromazine‐, bile duct‐ligated‐, α‐naphthylisothiocyanate‐, and lithocholic acid‐induced cholestasis (Cindoruk et al, ; Dai et al, ; El‐Sisi, Hegazy, & El‐Khateeb, ; Zhao, Yang, Liu, et al, ). In the present study, fenofibrate protected against sunitinib‐induced liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…Some pilot studies demonstrated the efficacy of fenofibrate and ursodeoxycholic acid combination in patients with primary biliary cirrhosis (Ghonem & Boyer, ; Zhang et al, ). Furthermore, fenofibrate could protect ethinylestradiol and chlorpromazine‐, bile duct‐ligated‐, α‐naphthylisothiocyanate‐, and lithocholic acid‐induced cholestasis (Cindoruk et al, ; Dai et al, ; El‐Sisi, Hegazy, & El‐Khateeb, ; Zhao, Yang, Liu, et al, ). In the present study, fenofibrate protected against sunitinib‐induced liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, gemfibrozil (0.375%) and fenofibrate (0.075%) were found to be effective against MS development. This dose was only 1/3–1/2 of the clinical dose level by comparing the trough concentration between mouse model and the clinical data . Risk of adverse reactions would be considerably decreased if this low dose is proven to be effective as well in the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…This dose was only 1/3-1/2 of the clinical dose level by comparing the trough concentration between mouse model and the clinical data. [38] Risk of adverse reactions would be considerably decreased if this low dose is proven to be effective as well in the clinic. So the dose-effect relationship found in this study was quite clinical relevant.…”
Section: Discussionmentioning
confidence: 99%
“…ANIT-induced intrahepatic cholestasis was established according to previous reports (Dai et al, 2017). Briefly, mice were randomized into two groups based on body weight.…”
Section: Identification Of Differential Paracrine Fgfs Between Anit-imentioning
confidence: 99%